Influence of boat tourism on the behaviour of Solovetskiy beluga whales (Delphinapterus leucas) in Onega Bay, the White Sea. Issue 10 (9th June 2020) - Krasnova, Vera V.; Prasolova, Ekaterina A.; Belikov, Roman A.; Chernetsky, Anton D.; Panova, Elena M.
Abstract: The influence of boat tourism on the beluga whale Delphinapterus leucas in the White Sea, Russia, was studied based on regular observations of belugas near the Solovetskiy Islands from 1995 to 2015. Changes in beluga behaviour, which were affected both by the distance between the boats and the whales and the character of boat activity (e.g. anchoring, drifting, or moving with the engine running) were observed. Boats following the belugas caused the greatest impact on the whales. This negative reaction was observed throughout all periods of observations. The results indicate the need to evaluate the potential long‐term, cumulative anthropogenic impact on beluga behaviour and the development of appropriate mitigation measures.